Training-test module in the system of pedagogical control of physical fitness in lower grades - Peleshenko, I.N. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to substantiate model characteristics of physical fitness of elementary school students of secondary schools through the introduction of training and test module in the pedagogical control. Material : the study involved 320 boys and 278 girls in grades 1-4 schools in Kharkov number number 57, 112, 166. Results : the level of physical fitness of elementary school students with available motor tests and the results are compared between the experimental data and control classes. Found that the introduction of educational test module in the process of physical education in the experimental classes has enhanced the level of physical fitness. In the experimental classes compared to the control classes, there was an increase of indicators (boys 22.2%, girls 24.6%). Conclusions : the introduction of educational test module in the pedagogical control for primary school pupils, will improve the physical fitness of children in the experimental classes, compared with controls, as well as to determine the averages on basic motor tests that can be used as a model characteristics of physical fitness.